Frequency of HIV Infection among Sailors in South of Iran by Rapid HIV Test - Hossain Jabbari; Somayeh Aghamollaie; Gholamreza Esmaeeli Djavid; Abbas Sedaghat; Maryam Sargolzaei; SeyedAhmad SeyedAlinaghi; Mehrnaz Rasoolinejad; Minoo Mohraz (AIDS Research and Treatment)
Information on the prevalence and risk factors for HIV infection among sailors is scarce. The aim of this seroprevalence study was to evaluate the frequency of HIV infection among sailors in south of Iran using rapid HIV test. The study included 400 consecutive participants in Lengeh, Shahid Rajaie, and Shahid Bahonar ports in south of Iran in May 2010. We observed only one case (0.25%) of HIV infection in this sample of sailors. While prevalence appears low at present, we recommend periodic HIV serosurveillance with detailed behavioral measures for this population in the future.